Gamochaeta beckii (Gnaphalieae, Asteraceae): a new species from Bolivia - Freire, Susana Edith (2013)
Gamochaeta beckii, a new species found in La Paz, Bolivia is described and illustrated. Gamochaeta beckii is similar to G. purpurea but it is easily distinguished by stems branched from the base to the inflorescence, oblanceolate leaves, the small capitula arranged in glomerules, forming leafy short and continuous spikes, and short acuminate inner phyllary apices. A key to the species of Gamochaeta occurring in Bolivia is presented.